Weak Efficiency of the Indonesian Share Market: Tests with Daily Data, 1983-1992 - Groenewold, Nicolaas; Ariff, Mohamed (The International Journal of Accounting and Business Society, 1995)
This  paper  sets  out test  of the  weak  Efficient  Markets  Hypothesis  (EMH) and  applies them  to  daily  data  for the  Indonesian  share  market.  Test  used include  traditional  tests  based  on  regression  and  correlation  procedure  as well  as  more  recent  test  for  the  non-stationarity  implications  of  the random-walk hypothesis,  viz,  the unit-root test and the  variance -ratio test. Results  are  assessed  for  sensitivity  with  respect  to  October  1987  Crash. There is evidence of predictability in the share-price index, violating the weak EMH.  Conclusions  are  not  greatly  affected  by  the  omission  of observations  for  October  1987  indicating  that  Indonesia  was  relatively isolated from the effects of the Crash.